A study of the relationship between perceived leadership styles and employees’ emotional intelligence / Siti Nur Azira Azmi - Azmi, Siti Nur Azira (Faculty of Business and Management, 2018)
The main objective of this study is to identify the relationship of perceived leadership styles and employees’ emotional intelligence. The leadership styles involved in this study is transformational leadership, transactional leadership and laissez-faire leadership. The respondent for this study was employees from SAJ Ranhill. Sdn. Bhd. with the total population of 250 persons. Hence, the value of 152 sample size was needed to analyze the data. The respondent who answered the questionnaires was consist of various department such as Human Resource, Water Quality and Administration as long as they are experience the perceiving leadership styles at the workplace and they are categorized among non-executive employees. The data collected using structural questionnaires from past researcher and it was distributed among 200 employees at SAJ Ranhill. Sdn. Bhd. and only 157 questionnaires was returned to the researcher while the rest number was considered lost. By using Statistical Package for Social Science, the data collected was used to run the data and analyze the findings. When the researcher gained the data, the data analysis activity was conducted in order to identify the relationship. Hence, the important table that contribute in this study is Pearson correlation and regression. Lastly, the findings of this study is the strong relationship that supported the objectives is transactional leadership styles while laissez-faire still significant to have a relationship with the dependent variables. The transformational leadership styles was not supported by the hypothesis of this study as the employees are reluctant to have a motivated and work hard leaders.